Publication Trends and Global Collaborations on Esophageal Atresia Research: A Bibliometric Study - Feng, Xiaoyan; Martynov, Illya; Suttkus, Anne; Lacher, Martin; Mayer, Steffi (European Journal of Pediatric Surgery, 2020)
Introduction Research on esophageal atresia (EA) has been heavily published over the past decades. Herein, we aimed to study the quantity and quality as well as key topics in EA research with regards to global collaborations among countries and authors.Materials and Methods Publications on EA from 1945 to 2018 were extracted from the Web of Science core collection database. Productivity (quantity) was assessed by the number of publications. Quality was estimated from the number of citations, citation rate per item and year, h-index, and impact index. Collaborative networks were evaluated using VOSviewer. All measures were analyzed for countries, authors, and journals. The 10 most cited original articles between 1969 and 2018 in 5-year intervals (n = 100) were manually screened to assess the key points of EA research.Results A total of 2,170 publications from 85 countries published in 388 journals were identified yielding 26,755 citations, both significantly increasing over time (p < 0.001). The most productive countries and authors also accounted for high-quality publications and benefited from an active global network. The most productive journals derived from the field of pediatric surgery but accounted only for one-third of EA papers. The best cited journals were unspecific for pediatric surgery. Long-term outcome remained the most important topic in EA research, followed by surgical techniques, epidemiology, associated anomalies, perioperative complications, and postnatal management. In contrast, basic science was underrepresented.Conclusion Over the past seven decades, EA publications increased tremendously. Productiveness and quality benefited from global networking. Long-term outcome remains the key interest of EA research.
Keywords: bibliometrics; citations; esophageal atresia; pediatric surgery